Digitalisasi Pemasaran dan Penguatan Pembukuan Sebagai Upaya Pengembangan UMKM Dodol Kareueut: Pengabdian - Apriyani, Deby; Adelia Putri Nur’aini; Nurlina, Sendri; Hadi, Yulianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
UMKM Dodol Kareueut in Tanjungsari Village, Pondok Salam District, Purwakarta Regency is a traditional food business that has been established since 1994. Although it carries cultural value and maintains a stable local market, this UMKM still faces several challenges, particularly in digital marketing and financial recording. This community service program is designed to strengthen the capacity of the business through digital marketing training and assistance in preparing simple bookkeeping. The implementation methods include observation, interviews, training sessions, hands-on practice, and monitoring. The results show an increase in the business owner’s understanding of using social media for promotion and the ability to manage a cash book using Excel. The output of this activity contributes to enhancing the competitiveness and sustainability of UMKM Dodol Kareueut.